An Examination of the Age Restriction of First-Time Voters in Indonesia's Elections From Maqashid Sharia Perspective - Faza, Amrar Mahfuzh; Putra, Dedisyah; Mafaid, Ahmad; Rizki, Juni Wati Sri (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
The age restrictions for first-time voters and the age requirements for electoral candidates in Indonesia have become topics of discussion and debate. One such debate revolves around the Constitutional Court's (MK) Decision Number 90/PUU-XXI/2023, which allows individuals under 40 years of age to run for president (capres) or vice president (cawapres), as long as they have experience as a regional head. The Supreme Court has also ruled on the minimum age for governor and deputy governor candidates, setting it at 30 years old, as outlined in Decision Number 23 P/HUM/2024. This study aims to analyze the shift in the paradigm regarding age restrictions for first-time voters in the context of Maqashid Syariah. The research employs a normative legal method with a statute approach to examine the paradigm shift in the regulation of age restrictions for voting rights and explores the implications of this shift on electoral justice and the integrity of political leaders, analyzed through the Maqashid Syariah approach. The findings of this study conclude that age restrictions on voting rights need to be relaxed, as age is no longer a determinant of a citizen's maturity in thinking. In Islam, politics is intended to bring about public benefit in line with the objectives of shariah, as the principle states that the actions of a leader towards their people must be based on the common good. The age restrictions need to be re-evaluated, considering the principle that the original legal status of something is its nonexistence, meaning that the original legal basis for age restrictions on voting and candidacy does not exist. Another principle suggests that legal rulings (fatwas) can change due to changes in time, place, conditions, and objectives (intent). Therefore, it is necessary to re-evaluate the paradigm shift in the regulation of age restrictions for first-time voters to ensure fair elections and local elections for both candidates and voters.